CORRELATION OF IgG AND IgM OLIGOCLONAL BANDS IN CSF AND SERUM WITH PROGRESSION AND DEGREE OF DISABILITY IN PATIENTS WITH MULTIPLE SCLEROSIS - Burnevska, Slobodanka Sazdova; Aleksovski, Vasko; Kuzmanovski, Igor; Boskovski, Bojan; Boskova, Tanja Petkovska; Tanovska, Nikolina (Journal of Morphological Sciences, 2020)
Objective: Our aim was to determine whether there was a correlation between IgG and IgM oligoclonal bands in CSF and serum and the EDSS score in patients with multiple sclerosis (MS). Methods: The material for this clinical, retrospective, and prospective, observational study consisted of patients with MS, treated at the University Clinic for Neurology, and outpatients followed in different stages of the disease. This study included 58 patients with confirmed MS diagnosis only. MS diagnosis was established according to widely accepted and revised McDonald's criteria for MS (MRI of the brain and spine, EP, routine laboratory blood tests) and who had a lumbar puncture during the diagnostic protocol. This paper included patients with various clinical forms of MS (RRMS, SPMS, PPMS). From all patients diagnosed with MS, demographic (age of onset of the first symptoms and sex) and clinical data (clinical course of the disease, duration of symptoms, degree of disability) were taken. The degree of disability was measured using a measurement scale of disability     Kurz (EDSS). Matched cerebrospinal fluid (CSF) and plasma samples were analyzed using isoelectric focusing and IgG specific immunofixation to test for the presence of intrathecal specific OCB. Results: OCB are important biomarkers that can support MRI diagnostics and help to avoid false-positive MS diagnoses. Therefore, the revised McDonalds criteria have increased the importance of OCB. Using both cross-sectional samples and serial sampling in a subgroup of patients   we found that the presence of CSF-restricted IgM OCB (but not of IgG OCB) was associated with an active inflammatory disease phenotype in PPMS patients. The presence of CSF IgM OCB may be a biomarker for a subset of PPMS patients with more active inflammatory disease, who may benefit from immune-directed treatments.   Keywords:oligoclonal bands, EDSS score, multiple sclerosis.